Estimation of Maximum Signal Strength for Satellite Tracking Based on the Extended Kalman Filter (Advances in Military Technology, 2023)
The article presents an improved satellite tracking approach using the extended Kalman filter within the control systems of the moving antenna. The main focus is on the issue of maintaining the maximum signal strength during vehicle movement, gyroscope and GPS sensors error and the deterioration of reception due to changing conditions (weather, obstacles). Typically used techniques are based on ad-hoc scanning of the maximum value of the RF signal. The approach presented in this article might be used as a much more consistent and elegant alternative to these algorithms. To prove the function of the presented algorithm, simulations of several different scenarios are performed. Based on these simulations, the robustness and speed of the newly designed algorithm are evaluated.
Keywords: antenna pointing; Matlab; mobile SATCOM; Kalman filter; simulation